Professional development activities among secondary school english teachers in Kuala Terengganu / Ruzana Omar - Omar, Ruzana (2009)
Annually, District Educational Department (PPD) and State Education Department (JPN) organize courses, workshops and various programmes that are related to the teaching of English for teachers who are teaching in schools in Kuala Terengganu. Though these teachers have attended these programmes for a number of years, few researches have been done to study how effective theses programmes are to the teachers and ultimately to the students as the end-receivers of the programme. The present study was conducted on 40 in-service teachers who are currently teaching English subject in secondary schools around Kuala Terengganu. This study adopted a research study of survey design and it was done to investigate on the criteria that drive in-service teachers to involve themselves in professional development activities, how do professional development activities affect the in-service teacher’s preparedness in their teaching and how do professional development activities affect their competence in teaching. The quantitative data from the questionnaires were analyzed using The Statistical Package for the Social Science (SPSS) for statistical analysis. Frequency analysis was applied to describe demographic data and numerical data for responses in every section of the questionnaire. The findings of Part 1 (Demographic data) revealed that the percentage of the male and female respondents was not equally distributed where the percentage of female outnumbered of those of male respondents. Results also indicated that a majority of the respondents were first degree holders and had between 11 to 20 years of teaching experience. The result’s analysis indicate that a majority of the respondents were aged between 41 - 50, teaching in suburban schools and English optionist teachers outnumbered to that non-optionist. The findings also revealed that “Enhance knowledge in English” as the main criteria that drove teachers to involve themselves in professional development and personal gains did not contribute much in driving them to involve in professional development activities. Results also showed that “Varying students activities in the classroom” has given the most effect to teachers in term of their preparedness in their teaching and ’’Study of English content” has most affected their competence in teaching.